2003
DOI: 10.1177/003172170308500109
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Democracy: What Schools Need to Do

Abstract: studied 10 educational programs whose objective-to develop democratic citizens-is largely ignored by school reform policy. Schools can fulfill this mission, they discovered, through specific strategies that promote civic commitments, capacities, and connections. BY JOSEPH KAHNE AND JOEL WESTHEIMER W HICH OF THE following headlines never appeared in a daily newspaper? a. Capital City Students Show No Gain in Reading, Math-Governor Threatens Takeover b. Middletown Schools to Be Taken Over by State for Failure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
12

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 0 publications
2
88
0
12
Order By: Relevance
“…Closer to home, students could elect class officers who will collaborate with the teacher on planning field trips and other special activities; or, they could as a class deliberate about and vote on issues including due dates for major projects, the order in which to read class novels, or the consequences for minor disciplinary infractions. Numerous examples, analyses, and evaluations of such approaches are available in the research literature (e.g., Weis & Fine, 2000;DarlingHammond, French, & Garcia-Lopez, 2002;Westheimer & Kahne, 2002;Kahne & Westheimer, 2003;Noguera, Ginwright, & Cammarota, 2006;Apple & Beane, 2007;Schultz, 2008;Cammarota & Fine, 2008;Delgado & Staples, 2008;Hess, 2009) and from practitioners and civic education organizations. (See www.campaignforthecivicmissionofschools.org for information about and links to over 100 well-vetted curricula, programs, and organizations.…”
mentioning
confidence: 99%
“…Closer to home, students could elect class officers who will collaborate with the teacher on planning field trips and other special activities; or, they could as a class deliberate about and vote on issues including due dates for major projects, the order in which to read class novels, or the consequences for minor disciplinary infractions. Numerous examples, analyses, and evaluations of such approaches are available in the research literature (e.g., Weis & Fine, 2000;DarlingHammond, French, & Garcia-Lopez, 2002;Westheimer & Kahne, 2002;Kahne & Westheimer, 2003;Noguera, Ginwright, & Cammarota, 2006;Apple & Beane, 2007;Schultz, 2008;Cammarota & Fine, 2008;Delgado & Staples, 2008;Hess, 2009) and from practitioners and civic education organizations. (See www.campaignforthecivicmissionofschools.org for information about and links to over 100 well-vetted curricula, programs, and organizations.…”
mentioning
confidence: 99%
“…Youth explore through participation ideas about who they can be and who they want to be as a member of the broader community, while building capacities, commitments, and social connections (Kahn & Westheimer, 2003) they need to succeed in their chosen roles. Flanagan (2003) found that participation, especially in diverse groups, can build a sense of belonging and social trust, a belief that "most people are fair, helpful, and trustworthy" (p. 167).…”
Section: Benefits Of Participationmentioning
confidence: 99%
“…Past research has shown those who are engaged in this way during adolescence are more likely to continue to actively engage throughout youth and adulthood (Colby & Damon, 1992;Haste, 2003Haste, , 2004Kahn & Westheimer, 2003;Pittman et al, 2007;Watts & Flanagan, 2007;Youniss & Hart, 2005;Youniss et al, 2002;Youniss & Yates, 1997). As people of all age, cultural and socioeconomic groups come to believe they can help shape organizations, communities and society, and actually have opportunities to do so, these institutions will come to more closely reflect the values and meet the needs of all their members (Sirianni and Friedland, 2001;Verba, Schlozman & Brady, 1995;Zeldin et al, 2007).…”
Section: Benefits Of Collective Actionmentioning
confidence: 99%
“…Although anxious to do good work, it is all too easy to adopt a charitable attitude that, while often well-intentioned, demonstrates that those doing the work feel superior because they have the answers to solve problems. Kahne and Westheimer (1996) describe this situation in terms of two competing models-charity and change-arguing that although both models may work, only the latter one enables people to work with others, to effect change and understand the underlying social issues and individual responsibilities. Linda Flower (1997) echoes this point.…”
Section: T E C H N I C a L P R O B L E M S O Lv I N G O R S E R V I C Ementioning
confidence: 99%